Using Wheat Flour and Alginate In Mozzarella Cheese Making On Physical and Sensory Quality - Purwadi Purwadi; Abdul Manab (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2014)
The purpose of this research was to know the best combination of using wheat flour and alginate on physical and sensory quality of Mozzarella cheese.The method that used in this research was factorial experiment with completely randomized design by using twelve treatments and three times repeatation. The variable measured was hardness, cutting point and sensory. The obtained data was analized by using analysis of variance continued by honesty significant difference (HSD).The result of this research showed that the used of wheat flour and alginate did not give a significance different interaction (P > 0,05) on the average of hardness, cutting point and sensory quality (colour, texture, and taste) of Mozzarella cheese, but used of wheat flour give a different significance effect (P < 0,05) on hardness and cutting point of Mozzarella cheese. The highest value was the treatment of T4A3, that was the combination of 7,5 % wheat flour and 1 % alginate.